VALIDATION OF THE MALAY VERSION OF THE EXPLANATORY MODEL INTERVIEW CATALOGUE STIGMA SCALE AMONG COVID-19 SURVIVORS IN MALAYSIA - Nik Ruzyanei, Nik Jaafar; Mohammad Farris Iman Leong, Abdullah; Nazirah, Azman; Nur Iwana, Abdul Taib; Noorsuzana, Mohd Shariff; Rohayu, Hami; Nor Shuhada, Mansor; Nizuwan, Azman (Faculty of Medicine, Universiti Malaya, 2022)
Abstract The Coronavirus disease (COVID-19) imparted unprecedented negative impact worldwide since it was declared as a global pandemic in 2020 due to its high infectivity and mortality rate. Consequently, those who have been infected with COVID-19 experienced significant amount of social stigma which resulting in deterioration of mental well being. Hence, this study aimed to translate the Explanatory Model Interview Catalogue Stigma Scale (EMIC-SS) into Malay and investigate the reliability and validity of the Malay version (EMIC-SS-M) among COVID-19 survivors in Malaysia. Initially, concurrent translation and back translation of the EMIC-SS was conducted followed by the assessment of its face and content validity. Then, the EMIC-SS-M was administered to 219 COVID-19 survivors recruited from three targeted centers for assessment of its reliability (internal consistency) and validity (convergent and discriminant validity, exploratory factor analysis [EFA] and confirmatory factor analysis [CFA]). The EMIC-SS-M reported an acceptable internal consistency with Cronbach’s α of 0.727, while its domains reported acceptable Cronbach’s α ranged from 0.708 to 0.795. EFA and CFA confirmed that the EMIC-SS-M consisted of 15 items in 4 domains. The EMIC-SS-M exhibited good psychometric properties and ready for use to assess stigma among COVID 19 survivors in Malaysia. It can be adapted for use to assess stigma in other disease conditions among the Malaysian population in future studies.